2007
DOI: 10.2135/cropsci2006.09.0576
|View full text |Cite
|
Sign up to set email alerts
|

The Long‐Term Impact of Phosphorus and Potassium Fertilization on Alfalfa Yield and Yield Components

Abstract: Addition of P and K fertilizer can increase alfalfa (Medicago sativa L.) yield and stand persistence, but the yield components associated with P‐ and K‐induced variation in agronomic performance are not clear. Our objectives were: (i) to determine the impact of P and K nutrition on productivity of a relatively old alfalfa stand; and (ii) determine which yield components are associated with changes in alfalfa forage yield. Treatments were a factorial combination of four P and five K rates replicated four times.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
69
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(94 citation statements)
references
References 33 publications
12
69
2
Order By: Relevance
“…Low-K status also had a significant impact on the disease tolerance and persistence of lucerne (Grewal & Williams 2003). Berg et al (2007) reported a significant improvement in lucerne herbage yield with the addition of P and K, and a marked improvement in lucerne persistence with K addition.…”
Section: Introductionmentioning
confidence: 96%
“…Low-K status also had a significant impact on the disease tolerance and persistence of lucerne (Grewal & Williams 2003). Berg et al (2007) reported a significant improvement in lucerne herbage yield with the addition of P and K, and a marked improvement in lucerne persistence with K addition.…”
Section: Introductionmentioning
confidence: 96%
“…Alfalfa is one of the most important forage crops worldwide because of its good forage quality, high forage yield in a wide range of environments, and high adaptability to different climatic conditions (Dordas, 2006;Berg et al, 2007;Zhang et al, 2008;Turan et al, 2009). Alfalfa is grown mainly for forage production while seed yield is secondary (Iannucci et al, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…As was noted by Berg et al (2005), direct P and K fertilization was consistently associated with greater mass of individual shoots. Low P and K soil fertility reduced fibre concentrations in the forage (Lissbrant et al 2009) as well as persistence and productivity (Berg et al 2007). As was highlighted by Chmelíková et al (2015), holistic analysis including above-and belowground traits should be used for the evaluation of fodder crops.…”
Section: Discussionmentioning
confidence: 99%
“…At the study site, altitude is 338 m a.s.l., the mean annual temperature is 8.2°C and the mean annual sum of precipitation is 422 mm (Prague-Ruzyně Meteorological Station, 1955-2007. The soil type was classified as illimerized Luvisol.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation